Policy Rules, Regime Switches, and Trend Inflation: An Empirical Investigation for the U.S. - Efrem Castelnuovo; Luciano Greco; Davide Raggi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
This paper estimates Taylor rules featuring instabilities in policy parameters, switches in policy shocks' volatility, and time-varying trend inflation using post-WWII U.S. data. The model embedding the stochastic target performs better in terms of data-fit and identification of the changes in the FOMC's chairmanships. Policy breaks are found not to be synchronized with variations in policy shocks' volatilities. Finally, we detect a negative correlation between systematic monetary policy aggressiveness and inflation gap persistence.
Keywords: E52; E61; E62; 330